DEVELOPMENT OF AN ATTENDANCE APPLICATION USING QUICK RESPONSE CODES BASED ON APPSHEET AT PT XYZ - Ulayya Antania Hanjani; Roni Faslah; Rayi Dwipanilih (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study aims to develop a digital attendance application based on AppSheet using Quick Response (QR) Code as a solution for recording employee attendance at PT XYZ. The development of this application is motivated by the fact that the attendance system is still manual and relies on CCTV monitoring, which is considered inefficient, inaccurate, and difficult to use for recapitulating employee attendance and overtime. The research method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques were carried out through observation, interviews, pre research questionnaires, and documentation studies. The results showed that the AppSheet based digital attendance application developed was capable of recording employee attendance in real time, automatically, and integrated with a cloud based database. This application also facilitated the attendance monitoring process by administrators and improved the neatness and accuracy of attendance data. Based on limited trials, the digital attendance system was deemed feasible and effective in improving the efficiency of employee attendance administration at PT XYZ.